The Artistic Concept “Нефтянка” (Oil Business) in O. Arukenova's Novel “The Rules of The Neftyanka (Eurasian Journal of Philology Science and Education, 2025)
Contemporary Kazakh prose is marked by the use and interaction of cultural codes, national and artistic concepts, and the personal biographies of authors. This article examines the artistic concept “нефтянка,” which forms the artistic integrity of O. Arukenova's book “The Rules of the Neftyanka”. The purpose of this study is to characterize the concept not only as a category in cognitive literary studies, which involves the study of literary texts as a special form of cognition and mental activity, but also to identify the ethnic and cultural uniqueness of this concept. The article aims to examine the cognitive features of the concept “нефтянка” and the ways in which it is represented through conceptual metaphors.Methodologically, we analyze metaphors and cognitive features of the concept presented in the figurative series identified in the artistic text, reflecting the main poetic elements of this story, such as the images of specialists from foreign companies and the location of oil companies. Through figurative relationships based on the hierarchy of boss/subordinate, local/foreign, cognitive signs appear that reflect the social aspects of life in modern society. The artistic concept “нефтянка” under consideration allows us to reveal the individual author's picture of the world, the functioning of intertext, irony, and simulacra images, and allows us to examine this text more deeply, because each author not only interprets the concept in his/her own way but also supplements and enriches its content with individual meanings. In this context, the concept “нефтянка” becomes not only the theme of the narrative but also a cognitive mechanism that organizes the perception of the text.Keywords: cognitive literary studies, artistic concept, national identity, conceptual metaphor.